Non-linear Relationships Between the Built Environment and Walking Frequency Among Older Adults in Zhongshan, China - Wu, Jiani; Zhao, Chunli; Li, Chaoyang; Wang, Tao; Wang, Lanjing; Zhang, Yi (Frontiers in Public Health, 2021)
Aim: Promoting walking activity is an effective way to improve the health of older adults. Frequency is a critical component of walking behavior and an essential determinant of daily walking levels. To decipher the association between the built environment and walking frequency among older adults, this study's aim is as follows: (1) to empirically test whether a nonlinear relationship between the two exists, and (2) to identify the threshold of the built environment characteristics that promote walking. Methods: The walking frequency of old adults were derived from Zhongshan Household Travel Survey (ZHTS) in 2012. The sample size of old adults aged 60 or over was 4784 from 274 urban and rural neighborhoods. A semi-parametric generalized additive model (GAMM) is used to analyze the nonlinear or non-monotonic relationships between the built environment and the walking frequency of older adults. Results: We found that the nonlinear relationships exist among five out of six built environment characteristics. Within certain thresholds, the population density, sidewalk density, bus-stop density, land use mixture, and the percentage of green space were positively related to older adults' walking trips. Furthermore, the land use mixture and the percentage of green space show an inverse V relationship. Conclusions: Built environment features can support and hinder the walking frequency of older adults. The findings in the current study contribute to effective land use and transport policies for promoting active travel among older adults.